Karma dan Objeknya Perspektif Vedanta - Dewi Wahyuningsih, Merliana (PANGKAJA: JURNAL AGAMA HINDU, 2019)
Karma is something that every human being must do. The karma that is carried out at this time will cause consequences in the future. This law of cause and effect is called the Karma Law. No one can avoid the wheel of rotation of Karma Law. God created the wheel of rotation of the Karma Law perfectly to regulate the process of all causal events that exist in the world. Therefore, no one can save someone from this turnaround, even God. The consequences of being rewarded depend on the cause done by a person depending on the motives of the Karma worked on. Cause and effect causes suffering in the form of dualism in life. The grief experienced by someone is generated from the virtual who shackles and causes Avidya or darkness. This article describes in detail how the relationship between karma and its object has an effect. The craving for a result in carrying out Karma also affects duality. In achieving lasting happiness is to transcend that duality, by diverting happiness which is only limited to the results of achieving eternal happiness by enjoying every process of karma done.